Consequences of influencer-created content on influencers’ authenticity in the beauty and personal care industry - DİRSEHAN, TAŞKIN; ERDOĞMUŞ, ZEYNEP İREM (My University, 2024)
One challenge in creating a personal brand is convincing consumers that it is authentic. Brands perceived to be inauthentic will have difficulty engaging with consumers; thus, the brand may not be long-lasting. This is also important for influencers, as they are a type of personal brand. Therefore, it is essential to consider the authenticity that is necessary for influencers when creating their brands. This study adapts the dimensions of advertising content value, and it examines the direct and indirect effects on influencer authenticity and followers’ trust, attitudes, and purchase intentions. The study reached out to 445 social media users interested in beauty and personal care products. The results indicate that the perceived entertainment and perceived informativeness of the influencer’s post content have a significant positive effect on influencer authenticity. Moreover, the results also show that influencer authenticity plays an important role in trust in and attitude toward branded posts. Finally, trust in and attitude toward branded posts lead to purchase intention.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Social Sciences and Humanities; Management; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; İşletme ve Uluslararası Yönetim; Sosyal Bilimler ve Beşeri Bilimler; Pazarlama; Business and International Management; Social Sciences & Humanities; Marketing; advertising content value; beauty and personal care (BPC) industry; influencer authenticity; Influencer marketing; Partial Least Squares Path Modeling (PLS-PM)